A new combination for the bembicine genus Selman Parker, 1929 (Hymenoptera: Crabronidae) - Rosa, Brunno B.; Melo, Gabriel A. R. (Zootaxa, 2014)
The identity of Monedula diana Handlirsch, 1890 is reassessed and the species is transferred to the monotypic genus Selman, which now includes two species, S. diana n. comb. and S. notatus (Taschenberg, 1870). The main differences between the two species are presented. Photographs of the holotype of Monedula diana are provided and its putative type locality is discussed. Also new distribution records are provided for S. notatus.